Prevalenee of anemia, iron, folie aeid and vitamin B12 defteieney in two Bari indian eommunities from westem Venezuela - Diez Ewald, María; Torres Guerra, Enrique; Layrisse, Miguel; Leets, Irene; Vizcaíno, Gilberto; Arteaga Vizcaíno, Melvis (Investigación Clínica, 2013)
The hematological status of 406 Bari indians from two communities was studied. One hundred and seventy nine individuals were from Campo Rosario a village located in a low arid plain south to the Perijá mountain range and 287 were from Saimadoyi, a fertile valley in the heart of the mountain. Anemia was found in 54% and 31% of the people from Campo Rosario and Saimadoyi respectively. Low serum iron was present in 28% of the population in both communities while low semm ferritin levels were encountered in 20% of the population from Campo Rosario and 5% of the people from Saimadoyi. A high prevalence of serum folate and vitamin B12 deflciency (91% and 64% respectively) was found in Campo Rosario, in contrast only 5% of the population from Saimadoyi had low folate and none were vitamin B12 deficient. While there was a positive significant correlation between hemoglobin and serum iron concentrations (r = 0.517, p < 0.001), no significative correlation was found between the other parameters studied. The high prevalence of anemia and nutrient deficiency among the Bari Indians, can be atributed to inadequate diets and the varied diseases encountered in the population.